FISHERY AND POPULATION DYNAMICS OF THE WINDOWPANE OYSTER, PLACENTA PLACENTA (LINNAEUS), FROM KAKINADA BAY - Narasimham, K A (Indian Journal of Fisheries, 2011)
The catch trends of the windowpane oyster at Yetimoga landing centreduring 1978-81 are described. The instantaneous rates of mortality of Placentaplacenta are estimated as Z = 4.0, M = 1.3 and F = 2.7. The life-span is 3.4years. The study on the yield in weight per recruit shows that under the current ftof0.89 year, the yield increases without reaching a maximum with increased F. Itis also observed that maximum yield can be obtained at tc i= 0.8 which is closeto the current value. It is recommended that the present tic and F can be maintainedwith advantage.